2017
DOI: 10.1016/j.eatbeh.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of shame, depression, and distress tolerance on the relationship between internalized homophobia and binge eating in lesbian and bisexual women

Abstract: There is limited research evidence about the specific factors influencing disordered eating for lesbian and bisexual women. Therefore, this study investigated relationships among binge eating, internalized homophobia, shame, depression, and distress tolerance in a sample of lesbian (n=72) and bisexual women (n=66). Two hypotheses were tested. First, it was hypothesized that shame and depression would mediate the relationship between internalized homophobia and binge eating. Second, it was hypothesized that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 53 publications
0
35
1
1
Order By: Relevance
“…The same tendency was found by Striegel‐Moore et al () in a college student sample. Conversely, no differences were found by Mason and Lewis () and Bayer et al () in volunteer samples.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The same tendency was found by Striegel‐Moore et al () in a college student sample. Conversely, no differences were found by Mason and Lewis () and Bayer et al () in volunteer samples.…”
Section: Resultsmentioning
confidence: 68%
“…As regards compensatory behaviours, Bayer et al () found no differences between the SM population and their heterosexual peers, nevertheless without providing any specific definition of the type of compensatory behaviour considered. On the other hand, fasting or dieting as compensatory behaviours was found to occur more frequently in the SM population in Matthews‐Ewald et al (), Hadland et al (), Watson et al (), and Zullig et al ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13, 14] Accordingly, researchers such as Bayer et al (2017), Wang and Borders (2016), and Watson et al (2016) examined how shame, concealing ones sexual orientation, and experiencing discrimination can elevate eating disorder risk among both sexual minority men and women. [1517] An in-depth review of the findings of studies that formally applied and tested theories and mechanisms underlying sexual orientation disparities is beyond the scope of this review, but a summary of the papers culled during the review is provided in Table 1.…”
Section: Theoretical Models For Sexual Orientation Disparitiesmentioning
confidence: 99%
“…Alternatively, Kaysen et al (2014) identified maladaptive coping, as defined by behavioral disengagement, denial, self-blame, selfdistraction, and substance use, as a mediator between IH and psychological distress in a large sample of queer women (n = 1,099). In another study, increased shame mediated the relationship between IH and binge eating among 138 lesbians and bisexual women (Bayer, Robert-McComb, Clopton, & Reich, 2017). Additional negative correlates of IH among queer women include emotional intelligence, coping resources, and feminist identification (Szymanski & Chung, 2003;Szymanski et al, 2008b).…”
Section: Internalized Heterosexismmentioning
confidence: 93%